Analytical Examination of the Philosophical Correlations between "Self-Knowledge" and "Knowledge of the Lord" with a Focus on the Relationship between Soul and Body - Mohammad Javad Jafari Zadeh; Mohammad Ali Vatandoost; Seyed Morteza Hosseini Shahroudi (حکمت اسرا)
Abstract One of the most important traditions regarding the connection between self-knowledge and the knowledge of God is the tradition "He who knows himself knows his Lord." This narration has been examined, explained, and analyzed by many Muslim thinkers. Among them, Allameh Hassan Zadeh Amoli, a contemporary philosopher and mystic, has elucidated 92 philosophical, mystical, and theological meanings for this tradition in one of his works. Among these interpretations, several aspects refer to the relationship between the soul and the body. The relationship between the soul and the body from various perspectives can lead to understanding the relationship between the Creator and the creation. In the present study, sixteen philosophical and mystical aspects of the relationship between the soul and the body and the relationship between the Creator and the creation have been discussed. The study concludes that numerous philosophical and mystical principles, such as "the existential encompassment of God over creatures, the causal origination of creatures from the Supreme Truth, God's comprehensive knowledge of creatures, the equal relation of the Supreme Truth to all parts of the universe, unity in lordship, minor and major resurrection, creation as a mirror for the Creator and the Creator for the creation, the management of the world with the world, the inherent obedience of creatures, etc.," can be inferred and proven through the relationship between the soul and the body.